2020
DOI: 10.1080/16078454.2020.1730557
|View full text |Cite
|
Sign up to set email alerts
|

The safety of modern intravenous iron infusions in patients with rheumatoid arthritis – a review of the literature

Abstract: Objectives: To assess the evidence for the safety of intravenous iron infusions in patients with rheumatoid arthritis. Methods: A systematic literature search was performed in June 2019 on PubMed and Cochrane databases for eligible studies. Results: There is significant evidence of safety and efficacy of intravenous iron in patients with rheumatoid arthritis using newer, less immunogenic iron preparations, such as iron sucrose and low molecular weight iron dextran preparations. Discussion: Iron deficiency anae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, importantly, oral supplementary strategies for functional iron deficiency remain more or less unsatisfactory, since iron absorption and export require FPN, which is degraded upon hepcidin production in response to inflammation. In addition, although parenteral iron supplementation appears to be safe in case of stimulated erythropoiesis, it was recently shown that at least the intravenous route of iron administration can even aggravate inflammation [21,22]. Accordingly, our data also argue against iron supplementation in inflammatory arthritis, but rather suggest a positive role of enteral iron restriction.…”
Section: Discussionmentioning
confidence: 56%
“…However, importantly, oral supplementary strategies for functional iron deficiency remain more or less unsatisfactory, since iron absorption and export require FPN, which is degraded upon hepcidin production in response to inflammation. In addition, although parenteral iron supplementation appears to be safe in case of stimulated erythropoiesis, it was recently shown that at least the intravenous route of iron administration can even aggravate inflammation [21,22]. Accordingly, our data also argue against iron supplementation in inflammatory arthritis, but rather suggest a positive role of enteral iron restriction.…”
Section: Discussionmentioning
confidence: 56%
“…The second peak occurs later when over 90% of low MW iron preparation has been taken up by macrophages, representing indirect ferroportin-mediated iron efflux from macrophages that fully saturates transferrin (Pathway II) [4] . Previous studies suggested that parenteral iron infusions mostly with iron dextran could exacerbate joint pain, synovitis, and arthralgia in patients with rheumatoid arthritis [5] . Accordingly, injection of iron dextran or sucrose led to significant exacerbation of joint inflammation along with iron deposition in the synovium of rats with adjuvant arthritis.…”
Section: Discussionmentioning
confidence: 99%
“… 144 Due to the resistance of FLS to ferroptosis and the redistribution of iron, iron supplementation in RA patients with iron deficiency anemia may lead to exacerbation of RA. 145 …”
Section: Ferroptosis and Rheumatoid Arthritismentioning
confidence: 99%
“…144 Due to the resistance of FLS to ferroptosis and the redistribution of iron, iron supplementation in RA patients with iron deficiency anemia may lead to exacerbation of RA. 145 Targeting ferroptosis has already shown positive effects in RA. Icariin can promote the SLC7A11-GSH-GPX4 axis to alleviate ferroptosis and lipopolysaccharide-induced synovitis.…”
Section: Ferroptosis and Rheumatoid Arthritismentioning
confidence: 99%